2000
DOI: 10.1111/j.1365-2621.2000.tb10255.x
|View full text |Cite
|
Sign up to set email alerts
|

Debittering of a Tryptic Digest of Bovine p‐casein Using Porcine Kidney General Aminopeptidase and X‐Prolydipeptidyl Aminopeptidase from Lactococcus lactis subsp. cremoris AM2

Abstract: The role of leucine aminopeptidase (LAP) from pig kidney cytosol and X-prolyldipeptidyl aminopeptidase (Pep X) from Lactococcus lactis subsp. cremoris AM2 in the hydrolysis and debittering of a tryptic digest of ␤ ␤ ␤ ␤ ␤-casein was studied. Hydrolysis was monitored by quantifying the release of primary amino groups and bitterness by use of a trained sensory panel. Sequential incubation of the bitter tryptic hydrolysate with LAP, Pep X and LAP resulted in higher levels of hydrolysis and significantly (P < 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
(14 reference statements)
0
7
1
Order By: Relevance
“…These results may be expected when the DH values of Alcalase containing hydrolysates were considered. It has previously been shown that hydrolysate bitterness increases with increasing DH (Barry, O'Cuinn, Harrington, O'Callaghan, & FitzGerald, 2000). According to the findings, this hypothesis cannot be entirely confirmed as the bitterness score of hydrolysate S8 decreased in the course of hydrolysis to a minimum of 3.4 (5 h), while the DH increased from 11.1% to 30%.…”
Section: Effects On the Bitternesscontrasting
confidence: 43%
“…These results may be expected when the DH values of Alcalase containing hydrolysates were considered. It has previously been shown that hydrolysate bitterness increases with increasing DH (Barry, O'Cuinn, Harrington, O'Callaghan, & FitzGerald, 2000). According to the findings, this hypothesis cannot be entirely confirmed as the bitterness score of hydrolysate S8 decreased in the course of hydrolysis to a minimum of 3.4 (5 h), while the DH increased from 11.1% to 30%.…”
Section: Effects On the Bitternesscontrasting
confidence: 43%
“…Bitterness in CNs following enzymatic hydrolysis has been linked to the release of hydrophobic peptides . In previous studies, increased bitterness of β ‐CN hydrolysed with trypsin and whey protein concentrate (WPC) hydrolysed with Alcalase 2.4 L, Prolyve 1000 and Corolase 7089 was reported at higher DH values. Similar results were seen herein with Alcalase, Prolyve and pepsin NaCas hydrolysates.…”
Section: Resultsmentioning
confidence: 99%
“…which lead to the generation of bitter peptides. Specific peptidolytic/proteolytic enzyme preparations have been linked with enhanced or reduced bitterness in CN hydrolysates . In addition, the degree of hydrolysis (DH) may play a role in overall hydrolysate bitterness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the food industry, Pro-containing peptides are associated with bitter flavours, yet few Pro-cleaving enzymes have been exploited to date in debittering [12][13][14][15]. The proline specificity of DPP IV suggests that it may have potential as a biocatalyst for peptide processing in-vitro.…”
Section: Introductionmentioning
confidence: 99%